Raising awareness among health educators and educational institutions of the need to overcome the language barrier among Non-Native English speaking students of Health Sciences in Qatar: A needs analysis and solutions - Ghizlane Bendriss (9025832) (2015)
Background Improving healthcare starts by providing the best education possible for medical students. In the Gulf region, a new movement known as “Arabization of Health Sciences” is at the root of many of the last educational reforms regarding the language in the teaching of sciences. Those reforms created a non-negligible gap among medical students in terms of scientific terminology. Research questions This report aims to answer two questions: 1) What is the nature of the language barrier facing non-native English speaking students in their understanding of biological terminology? 2) How can non-native English speaking students overcome this language barrier and what learning tools can be used to do that? Method Study participants were enrolled in a foundation and a premedical program at a U.S. medical university located in Qatar. A questionnaire was proposed to students asking for: 1- their need for translation of scientific terms, 2- the language of study of sciences in high school, 3- their shyness in asking the meaning of a scientific term, 4- the usefulness of a bilingual English-Arabic glossary with Latin/Greek origins of the terms. Results Survey indicates that 72% of the students who went through the foundation year since 2012 did experience at least “sometimes” the need for translation of scientific terms into Arabic. This need for translation is related to the language used to study sciences in high schools. This study showed a decrease in 2014 for the proportion of students in the foundation year that studied sciences in English with 73% in 2013 to 39% in 2014. Also, 61% of students enrolled in the foundation program in 2014 refrained from asking questions about the meaning of a term because of shyness. Finally, foundation and Premed-1 students agreed respectively with 80% and 83% on the usefulness of having, for their premedical studies in biological sciences, a glossary with English-Arabic translations and Latin/Greek origins of terms, and 64% opted for having preferentially both an application and a booklet formats for the glossary. Conclusion These results raise awareness regarding a “Double Language Barrier” (DLB) pattern for Arabic-speaking students. Indeed, medical and biological terminology, before being “scientific English” is derived from Latin and Greek, two languages that are taught neither in English-speaking schools nor in Arabic-speaking schools. To this end, the authors propose a practical tool for educational institutions in Qatar and in the Gulf region to foster innovative ways of teaching health sciences to Arabic-speaking students. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.1